FILSAFAT AKHLAK DALAM KONTEKS PEMIKIRAN ETIKA MODERN DAN MISTISISME ISLAM SERTA KEMANUSIAAN - Ipandang, Ipandang (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
In the context of modern ethical thinking, philosophy of Akhlak occupies animportant role. Philosophy of Akhlak will form a state of the soul that can bring aperson to good deeds. In this modern era, there are still a few researcers who research the philosophy ofakhlak, because they have been satisfied with akhlak from religion and do not feel the need for scientific research on the basis of good and bad. In fact, moral philosophy is focused on the view toward improvement in determining the rights and obligations, and generate personal feelings about the great responsibility for self, society and God